Nilai Kearifan Lokal Kesenian Bantengan dalam Implementasi Akuntansi - Sopanah, Ana; Hermawati, Adya; Bahri, Syamsul; Utami, Riski Nur; Sulistyan, Riza Bahtiar (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Research objective: This study aims to explore local wisdom in Bantengan art and analyze accounting records of transactions that occur during the implementation of Bantengan art. Method/approach: The type of method used is a qualitative method with an ethnomethodological approach, where the author analyzes a culture in the form of the art of "Bantengan," focusing on the "Reality" or the social aspects of everyday life. Results: The results of the study show that Bantengan art contains values ​​of wisdom, including "Nguri-uri Budaya, Guyup Rukun, Modal Sosial." These three values ​​are implemented in the costs for cultural preservation, transparency in financial reporting, and voluntary costs. Implications of the practice: This research has identified local wisdom and successfully traced accounting practices in the bantengan art. Originality/novelty: This research combines the results of local wisdom values ​​with accounting science which has never been done in Bantengan art.